PEMBERIAN INTERVENSI SENAM LANSIA PADA LANSIA DENGAN NYERI LUTUT - Afifka Dyah Ayu D; Bambang Edi Warsito (Jurnal Keperawatan Diponegoro, 2012)
Aging is a process of eliminating the network's ability to repair itself gradually. Elderly tend to get the decreased on the musculoskeletal system. The decreased of the musculoskeletal system is characterized by pain in the joints, for example the knee joint. Knee pain is a regenerative joint diseaseand also one signs and symptoms of osteoarthritis. One way to reduce the knee pain is using the non-pharmacologic therapy with elderly gymnastic. The purpose of this research is to provide elderly exercise intervention in older adults with knee pain to reduce the pain. The benefit of this research is to train the ability of muscles and joints to reduce the knee pain scale in the elderly. The method used a quantitative research design with experimental and one type of group pre-post test design. The population in this study were elderly men and women in the Social Rehabilitation Unit "Margo Mukti" Rembang District.The instrument used a VAS pain scale or Baourbanis and observation sheet. Sampling used a minimum number of samples for quantitative experimental studies as many as 15respondents. Implementation of the elderly gymnastic can be done in the morning before breakfast for about 15 - 45 minutes. The research was conducted on February 27, 2012 until March 3, 2012 at the Social Rehabilitation Unit "Margo Mukti” Rembang District. This study used a statistical test of Wilcoxon. The resultof this research showed that the significance p-value 0.001, which means the sig <α = (0.05). It was concluded that elderly gymnastic are effectively overcome the knee pain in elderly at the Social Rehabilitation Unit"Margo Mukti" Rembang District and this elderly gymnastic is expected to help community to reduce the knee joint pain